Makna Banten Sesayut Dalam Pelaksanaan Upacara Magedong-Gedongan - Desak Ketut Wismayani; Ni Luh Putu Yuliani Dewi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Humans always crave a prosperous and happy life, pure in body and mind, to make it happen, humans must maintain a harmonious relationship with the creator (God), with fellow humans and with the surrounding natural environment. Yajña ceremonies are divided into several types, one of which is manusa yaja, in manusa yaja there is a magedong-gedongan ceremony which requires upakara/banten facilities, namely banten sesayut. Magedong-Gedongan is a ceremony carried out to ask for the safety of babies who are still in the womb, so they can stay healthy until they are born in the world. In the implementation of this magedong-gedongan ritual, one of the offerings is the offering of offerings, one of which is the sesayut banten, this offering is a sthna of Ista Dewata to ask for serenity so that people who carry out the yaja are protected from harm, disturbance, or disease and so on. Sometimes people who carry out this magedong-gedongan ritual only know the ceremony, without thinking about the meaning of the offering used. Therefore, the author's purpose in making this article is to provide an understanding for Hindus who will carry out the magedong-gedongan ceremony related to the meaning of the ceremony itself and the meaning of the sesayut banten used in the magedong-gedongan ceremony. Banten sesayut has a function as a symbol of sincerity in carrying out the yajña ceremony and has the meaning of balance and the meaning of harmony. This study uses a qualitative approach and data collection methods in this study using library research, data sourced from books are used as references and efforts to analyze things that are considered related to the topics discussed in this study. With this research, it is hoped that it can provide new knowledge about the meaning of banten sesayut.